Formação continuada para educação infantil em municípios da região de Laguna-SC (AMUREL) - Souza, Eloisa Filet de; Buss-Simão, Márcia (Revista Cocar, 2018)
As ponderações tecidas neste texto trazem um recorte de uma pesquisa de Mestrado já finalizada, a qual teve como foco investigar como é desenvolvida a formação continuada das profissionais de educação infantil nos municípios da Associação de Municípios da Região de Laguna (AMUREL), de forma a analisar se as iniciativas e estratégias têm garantido o direito a formação continuada destas profissionais. Visando alcançar tal objetivo, recorreu-se a um questionário para recolha dos dados, o qual foi enviado aos 18 municípios que compõem a região pesquisada, dentre estes, 16 municípios o responderam e compuseram o conjunto de dados que foram analisados. Nos limites deste artigo a intenção é analisar as iniciativas, estratégias e parcerias que garantem a formação continuada das profissionais de educação infantil da Região de Laguna (AMUREL). Palavras-chave: Educação infantil. Formação Continuada. Região da AMUREL. Continuing education for early childhood education in municipalities in the region of Laguna-SC (AMUREL) " Abstract The weightings presented in this text are a summary of an already completed Master's research, which focused on investigating how the continuing formation of professionals of children's education is developed in the municipalities of the Association of Municipalities of the Laguna Region (AMUREL), to ensure that the initiatives and strategies have guaranteed the right to continuous training of these professionals. Aiming at reaching this objective, a questionnaire was used to collect the data, which was sent to the 18 municipalities that make up the researched Region. Of these, 16 municipalities answered the questionnaire and composed the data. Within the limits of this article, the intention is to analyze the initiatives, strategies and partnerships that guarantee the continuous training of nursery education professionals in the Laguna Region (AMUREL). Keywords: Child education. Continuing Education. Region of AMUREL. "